Synthesis and enhanced gas sensing properties of flower-like ZnO/α-Fe2O3 core-shell nanorods. Issue 8 (1st June 2017) - Zhang, Bowen; Fu, Wuyou; Meng, Xianwei; Ruan, A.; Su, Pengyu; Yang, Haibin
Abstract: This paper reports a facile two-step synthesis route for the preparation of flower-like ZnO/α-Fe2 O3 nanorods (NRs). Flower-like ZnO NRs with the average diameter about 810 nm and length about 4.5 µm were firstly synthesized via a chemical solution method, and then ZnO NRs was coated with a continuous α-Fe2 O3 layer to form ZnO/α-Fe2 O3 core-shell structure through an ionic-layer adsorption and reaction method. The gas-sensing results show that the ZnO/α-Fe2 O3 NRs exhibit excellent sensitivity, selectivity, and response-recovery capacity to ethanol vapor at a low optimum temperature of 240 °C. In particular, compared with pure ZnO NRs and α-Fe2 O3 nanoparticles (NPs), the ZnO/α-Fe2 O3 NRs show an obvious improvement in gas sensing properties. The substantial improvement of sensing properties may be attributed to the unique microstructure and heterojunction formed between ZnO and α-Fe2 O3 .